C135.100-2024 - IEEE Standard for Line Hardware for Overhead Line Construction (IEEE, 2025)
Covered in this standard are the requirements for line hardware used in overhead lines, including clevis and eye fittings, Y-clevis fittings, socket fittings, ball fittings, chain links, shackles, triangular and rectangular yoke plates, suspension clamps, strain clamps, straight-line deadend clamps, and shoulder live-line extension links.